Peningkatan Hasil Belajar Fisika Siswa Melalui Model Pembelajaran Kooperatif Tipe Jigsaw di Kelas XI IPA/3 SMAN 1 Ulakan Tapakis - Zulbaidah, Zulbaidah (Jurnal Pendidikan Nasional, 2021)
This study aimed to obtain information about improving students' physics learning outcomes through the jigsaw type cooperative learning model in Class XI. IPA/3 SMAN 1 Ulakan Tapakis. The research was carried out in Class XI. IPA/3 SMAN 1 Ulakan Tapakis. Types of classroom action research (CAR). The research subjects were class XI IPA/3SMA Negeri 1 Ulakan Tapakis with 27 students consisting of 23 female students, and 4 male students. The research procedure for each cycle is planning, implementation, observation and reflection. The research instruments were observation, questionnaire, pretest, posttest, and daily notes. Data analysis technique is descriptive analysis. The results showed that the data on the number of students who completed as many as 24 with a percentage of 89% and students who did not complete as many as 3 students with a percentage of 11%. Furthermore, these results indicate that in the second cycle classically students have finished studying, because students who get a score of 76 are already 89% greater than the desired percentage of completeness, which is 85%. Thus, in conclusion the learning process using the jigsaw type cooperative learning model can improve student learning outcomes in class XI IPA/3 SMA Negeri 1 Ulakan Tapakis.